Ophthalmic parameters in adult Shih Tzu dogs - Karina Kamachi Kobashigawa; Tiago Barbalho Lima; Ivan Ricardo Martinez Padua; Alexandre Augusto Franchi de Barros Sobrinho; Fabio de Andrade Marinho; Kethye Priscila Ortêncio; José Luiz Laus (Ciência Rural, 2015)
Ocular surface diseases are often diagnosed in brachycephalic dogs. The ophthalmic parameters of the Shih Tzu dogs are evaluated in this study since this breed is among the most commonly affected by these diseases. In this study, ophthalmic parameters of this breed were partly studied under physical restraint. Schirmer tear test, breakup time test, aesthesiometry, biomicroscopy, non-contact specular microscopy, laser flaremetry, applanation tonometry, ultrasonography and ophthalmoscopy were carried in 48 eyes of 24 male and female dogs, aged from two to four years, weighing between 5 and 10kg. All dogs were from a breeding kennel. Descriptive statistics were applied to the data. Mean and standard error for Schirmer tear test was 26.145±0.803mm min-1; breakup time test, 13.668±0.538s; and aesthesiometry, 2.395±0.071cm. The biomicroscopy evaluation showed that 70.83% of the eyes had medial entropion; 42% caruncular trichiasis; 33% distichiasis, 27% mild paracentral corneal opacity; and 13% corneal melanosis. Mean and standard error for endothelial cell density was 2221.591±20.161cells mm-2; endothelial cell hexagonality, 63.770±1.805%; endothelial cell area, 451.895±4.179mm2; central corneal thickness, 0.490±0.007 mm; laser flaremetry, 1.720±0.216PC ms-1; applanation tonometry, 16.118±0.460mmHg; axial length, 20.255±0.134mm; lens thickness, 6.624±0.031mm; anterior chamber, 4.064±0.109mm; and vitreous chamber, 9.565±0.054mm. Ophthalmoscopy findings were not different from previous reports for other breeds. The results showed that the ophthalmic Shih Tzu parameters did not differ from other breeds according to data in the literature, except for the breakup time and Cochet-Bonnet aesthesiometry.